KTIRIK ATAS ORIENTALIS DALAM INTERPRETASI HADIS - Syafi'in Mansur; Salim Rosyadi (Holistic al-Hadis, 2022)
The purpose of this research is to illustrate that Orientalist studies and interpretations of the Prophet's Hadith or Sunnah are positive and negative. Positive Orientalist studies and interpretations are not polemical, but sympathetic and academically good and enlightening. While the study and interpretation of the negative Orientalists brought polemics both among the Orientalists themselves and among Muslim intellectuals. The Orientalist who brought this polemic, is due to untruthfulness, dishonesty and objectivity so that the Orientalist gets sharp criticism from Muslim intellectuals, both inclusive, exclusive and modernist. All of that, aimed at Orientalists studying and interpreting the Hadith of the Prophet and the Sunnah with a scientific and systematic purpose, not for their personal, group and religious interests.